PENGARUH POLITIK DALAM PEMBENTUKAN HUKUM DI INDONESIA - Imawanto Imawanto; Edi Yanto; Fahrurrozi Fahrurrozi; Yulias Erwin (Universitas Muhammadiyah Mataram, 2021)
The development of law in Indonesia is determined by the political configuration between the legislature and the executive. Nearly 85 percent of the People's Representative Council tends to close or qualify with the executive. When the executive submits draft legislation, it is immediately approved by the Indonesian Parliament. The urgency of the research is to determine the influence of politics on the formation of law in Indonesia. What is the political configuration and character of Indonesian legal products and their re-actualization and formulation? The research method used is normative research through library research and a statutory approach. The research shows that currently, in Indonesia, the political dominance of the law is getting stronger. A political party that should be the incarnation of the people's will only appear to be a vehicle to gain or maintain power. This results in legal products produced only by political interests and certain groups, without paying attention to their suitability with the objectives of the State. The historical movement of the transition of Islamic law in Indonesia is full of various historical, philosophical, political, sociological, and juridical dimensions. In fact, Islamic law in Indonesia has fluctuated in line with the politics of law practiced by state authorities. This is based on the socio-cultural strength of the majority of the Muslim community in Indonesia. There is interaction in terms of political decisions, thus giving rise to various political decisions to benefit the Islamic community itself. In Indonesia, there is a determinant politics of law. This means that law is a variable that is influenced by politics. The situation and the political policies that took place greatly influenced the Islamic community's attitudes.Keywords: Politics; Law; Indonesia. ABSTRAKPerkembangan hukum di Indonesia ditentukan oleh konfigurasi politik yang terjadi antara legislatif dan eksekutif. Kecenderungan Dewan Perwakilan Rakyat hampir 85 persen merapat atau berkualisi dengan eksekutif, sehingga ketika eksekutif mengajukan draf perundang-undangan langsung di setujui DPR RI. Urgensi penelitian untuk mengetahui pengaruh politik terhadap pembentukan hukum di Indonesia. Bagaimana konfigurasi politik dan karakter produk hukum Indonesia, dan reaktualisasi dan formulasinya. Metode penelitian yang digunakan adalah penelitian normatif, melalui penelitian kepustakaan dan pendekatan perundang-undangan. Hasil penelitian, bahwa saat ini di Indonesia, dominasi politik terhadap hukum semakin menguat. Partai politik yang seharusnya menjadi penjelmaan kehendak rakyat, hanya terkesan menjadi kendaraan untuk memperoleh maupun mempertahankan kekuasaan. Hal ini berakibat pada produk hukum yang dihasilkan hanya sesuai dengan kepentingan-kepentingan politik dan golongan tertentu, tanpa memperhatikan kesesuaiannya dengan tujuan Negara. Pergerakan sejarah peralihan hukum Islam di Indonesia, penuh dengan berbagai macam dimensi historis, filosofis, politik, sosiologis dan yuridis. Faktanya, hukum Islam di Indonesia telah naik turun sejalan dengan politik hukum yang di praktekan oleh penguasa negara. Hal tersebut besumber pada kekuatan sosial budaya mayoritas masyarakat Islam di Indonesia. Adanya Interaksi dalam hal putusan politik, sehingga memunculkan berbagai keputusan politik bagi kepentingan masyarakat Islam itu sendiri. Di Indonesia terjadi politik determinan atas hukum. Artinya bahwa hukum adalah variabel yang terpengaruhi oleh politik. Situasi dan kebijakan politik yang berlangsung sangat mempengaruhi sikap yang harus di ambil oleh masyarakat Islam.